Evaluation of the doctoral program in medical education of Isfahan University of Medical Sciences based on the CIPP model - Samira Derakhshanfard; Fariba Jokar; Soheyla Ehsanpour; Arash Hadadgar (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Continuous evaluation is necessary to achieve appropriate quality in educational programs. The aim of this study was to evaluate the doctoral program of medical education at Isfahan University of Medical Sciences based on the CIPP model. MATERIALS AND METHODS: This descriptive and educational evaluation study was conducted in 2020 at Isfahan University of Medical Sciences. The study population consisted of all heads of department, faculty members, students, and PhD graduates of medical education from 2010 to 2020 who were enrolled in the study by census method. The data collection tool was a researcher-made questionnaire of CIPP evaluation model which was used when validity and reliability of them were confirmed. The data obtained from the questionnaires were analyzed in two levels of descriptive statistics of mean and standard deviation and inferential statistics one-sample t-test. RESULTS: Based on the CIPP model, the mean evaluation scores from the perspective of the heads of department, faculty members, and graduates were 4.1 ± 0.1, 3.64 ± 0.42, and 3.33 ± 0.66, respectively, which were significantly higher than the average (P ≤ 0.05). However, the mean evaluation score was not significantly higher than the average from the viewpoint of the students (3.24 ± 1.17). CONCLUSION: Based on the results of the study, the status of the doctoral course in medical education at Isfahan University of Medical Sciences was assessed as appropriate by the subjects of the study including the heads of department, faculty members, and graduates. It was not, however, acceptable according to the students. Based on the results, it is suggested that evaluation be done continuously and measures are taken to correct the weaknesses and enhance the strengths.